Informational Cascades and Decision to Migrate - Gil S. Epstein (Institute for the Study of Labor (IZA), 2002)
We introduce the idea that informational cascades can explain the observed regularity that emigrants from the same locations also tend to choose the same foreign locations. Thus informational cascades generate herd behavior. Herd behavior is compared with the network externalities explanation of the same phenomenon. The relation between social tensions and herd behavior is observed when local populations are xenophobic.
Keywords: J61; F22; 330; Migration; informational cascades; herd behavior; xenophobia; network externalities; Wohnstandort; Migranten; Informationsverhalten; Soziales Netzwerk; Theorie